Reduction of EMI with chaotic space vector modulation in direct torque control - Asker, Mehmet Emin; Özer, Ahmet Bedri; Kürüm, Hasan (My University, 2016)
Due to asymmetric three-phase system and influence of inverter nonlinearity, large torque and stator flux harmonics would exist in the space vector modulation based direct torque controlled (DTC-SVM) three-phase permanent magnet synchronous machines (PMSMs). A general expression for electromagnetic torque is derived for DTC of asymmetric three-phase PMSMs considering the influence of inverter nonlinearity. To mitigate the influence of the undesired harmonics, a compensation method is developed by enhancing the standard PI-regulator in the torque and flux loops with appropriate resonant controllers. Since the second and sixth order harmonics are the most dominant components, two resonant controllers tuning at the 2nd and 6th of stator angular frequency, respectively, are utilized. The proposed method can achieve good steady-state performance in terms of low torque and flux ripples, while keeping the merits of the conventional DTC-SVM strategy such as good dynamic torque response and machine parameter independence. The experimental results validate the effectiveness of the proposed strategy.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Torque; Stators; Harmonic analysis; Inverters; Couplings; Rotors; Electromagnetics